Acute and late changes in intraarticular cytokine levels following anterior cruciate ligament injury. Issue 2 (6th August 2012) - Bigoni, Marco; Sacerdote, Paola; Turati, Marco; Franchi, Silvia; Gandolla, Marta; Gaddi, Diego; Moretti, Sarah; Munegato, Daniele; Augusti, Carlo A.; Bresciani, Elena; Omeljaniuk, Robert J.; Locatelli, Vittorio; et al.
Abstract Surgical reconstruction of the anterior cruciate ligament (ACL) does not necessarily decrease the risk of developing osteoarthritis (OA). The inflammatory response and relative changes in pro‐ and anti‐inflammatory cytokines could participate in triggering the development of OA. To test this hypothesis we measured the concentrations of IL‐1β, IL‐1ra, IL‐6, IL‐8, IL‐10, and TNF‐α at different times after ACL rupture. The sample population consisted of 48 patients with ACL tear which were assigned to different groups according to the time elapsed from the injury: 22 acute (A), 7 early sub‐acute (ESA), 11 late sub‐acute (LSA), and 8 chronic (C). In group A, there were high levels of IL‐1β, IL‐6, and IL‐8, whereas levels of IL‐1ra and TNF‐α were significantly lower than usually reported. IL‐1β and IL‐8 concentrations returned with time to normal levels in the ESA group. Interestingly, IL‐1ra levels remained always significantly lower than normally reported levels, and TNF‐α levels did not increase after trauma. Our data show increased level of pro‐inflammatory cytokines (IL‐6 and IL‐8) in the acute phase of inflammation which could be responsible for triggering cartilage catabolism and suggest that prompt neutralization of IL‐6 and IL‐8 accumulations in synovial fluid could help prevent development of OA in ACL‐injured knees. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 315–321, 2013